Immigration policy and entrepreneurship - Stéphane Mahuteau; Matloob Piracha; Massimiliano Tani; Matias Vaira Lucero (Institute for the Study of Labor (IZA), 2011)
This paper analyses the impact of a change in Australia's immigration policy, introduced in the mid-1990s, on migrants' probability of becoming entrepreneurs. The policy change consists of stricter entry requirements and restrictions to welfare entitlements. The results indicate that those who entered under more stringent conditions - the second cohort - have a higher probability to become self-employed, than those in the first cohort. We also find significant time and region effects. Contrary to some existing evidence, time spent in Australia positively affects the probability to become self-employed. We discuss the intuitions for the results and their policy implications.
urn:nbn:de:101:1-201202285070
Keywords: C34; J24; J61; 330; immigration policy; entrepreneurship; migration; Migrationspolitik; Unternehmensgründung; Migranten; Australien